LOFAR detections of low-frequency radio recombination lines towards Cassiopeia A - Asgekar, A.; Oonk, J.; Yatawatta, S.; van Weeren, R.; McKean, J.; White, G.; Jackson, N.; Anderson, J.; Avruch, I.; Batejat, F.; Beck, R.; Bell, M.; et al. (EDP Sciences, 2013)
Cassiopeia A was observed using the low-band antennas of the LOw Frequency ARray (LOFAR) with high spectral resolution. This allowed a search for radio recombination lines (RRLs) along the line-of-sight to this source. Five carbon a RRLs were detected in absorption between 40 and 50 MHz with a signal-to-noise ratio of >5 from two independent LOFAR data sets. The derived line velocities (vLSR ~ - 50 km s-1) and integrated optical depths (~13 s-1) of the RRLs in our spectra, extracted over the whole supernova remnant, are consistent within each LOFAR data set and with those previously reported. For the first time, we are able to extract spectra against the brightest hotspot of the remnant at frequencies below 330 MHz. These spectra show significantly higher (15-80 percent) integrated optical depths, indicating that there is small-scale angular structure of the order of ~1 pc in the absorbing gas distribution over the face of the remnant. We also place an upper limit of 3 × 10-4 on the peak optical depths of hydrogen and helium RRLs. These results demonstrate that LOFAR has the desired spectral stability and sensitivity to study faint recombination lines in the decameter band.